Comparison of perioperative characteristics and prognostic performance in patients with pulmonary lobectomy in early or later period after percutaneous coronary intervention - Yun, Tianyang; Tang, Yue; Yang, Bo; Li, Ke; Liang, Tao; Yin, Dongtao; Liu, Yang (Translational Cancer Research, 2019)
Background: In order to analyze the feasibility of pulmonary lobectomy for non-small cell lung cancer (NSCLC) in early period after percutaneous coronary intervention (PCI), the current study was designed to compare perioperative characteristics and prognostic performance of patients with pulmonary lobectomy within 3 months or 3 months later after PCI. Methods: This study enrolled 349 patients simultaneously with NSCLC and coronary stenosis. There were 198 and 151 patients with pulmonary lobectomy within 3 months or 3 months later after PCI, respectively. Results: Age of all patients was 62 [53–75] years. There was no difference in demographic characteristics, medical histories, cancer locations and stent numbers between two groups (P>0.05 for all). Operation time, blood loss and hospital stay after pulmonary lobectomy had no difference between two groups (P>0.05 for all). Compared with those with pulmonary lobectomy 3 months later after PCI, survival rate during 5 years after pulmonary lobectomy was significantly higher in patients with pulmonary lobectomy within 3 months after PCI (P